1994
DOI: 10.1139/b94-153
|View full text |Cite
|
Sign up to set email alerts
|

Small-subunit rRNA gene sequences from representatives of selected families of the Gigartinales and Rhodymeniales (Rhodophyta). 1. Evidence for the Plocamiales ord.nov.

Abstract: Nucleotide sequences of the nuclear, small-subunit (SSU) ribosomal RNAs, as inferred from polymerase chain reaction (PCR)-amplified products, are presented for Areschougia congesta (Turner) J. Agardh (Solieriaceae), Dasyphloea insignis Montagne (Dumontiaceae), Sarcothalia crassifolia (C. Agardh) Edyvane & Womersley (Gigartinaceae), Nizymenia australis Sonder (Nizymeniaceae), Phacelocarpus peperocarpos (Poiret) Wynne, Ardré & Silva (Phacelocarpaceae), Plocamiocolax pulvinata Setchell, Plocamium angustum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
155
0
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 39 publications
2
155
0
3
Order By: Relevance
“…The Plocamiales was removed from the Gigartinales based on a combination of molecular and anatomical data (Saunders & Kraft, 1994). Since then, molecular studies using SSU (Saunders & Kraft, 2002;, LSU (Harper & Saunders, 2001b) and combined SSU þ LSU analyses (Harper & Saunders, 2001b) have continued to support the independence of this order.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Plocamiales was removed from the Gigartinales based on a combination of molecular and anatomical data (Saunders & Kraft, 1994). Since then, molecular studies using SSU (Saunders & Kraft, 2002;, LSU (Harper & Saunders, 2001b) and combined SSU þ LSU analyses (Harper & Saunders, 2001b) have continued to support the independence of this order.…”
Section: Discussionmentioning
confidence: 99%
“…Saunders et al, 1994). Lindstrom (1987) proposed the monogeneric family Acrosymphytaceae removing Acrosymphyton from the Dumontiaceae (Gigartinales) based on differences in female reproductive structures and post-fertilization development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR amplification of the nSSU rDNA region was performed by amplification of two overlapping fragments. Fragment R, *1170 bp in size, was amplified by primers 18e (Hillis & Dixon, 1991) and NS4 (White et al, 1990) and fragment Qs, *850 bp in size, by primers G04 (Saunders & Kraft, 1994) and J04 (Broom et al, 1999) as shown in Fig. 2.…”
Section: Molecular Analysismentioning
confidence: 99%
“…Reaction products were purified by PEG precipitation and sequenced on an ABI 377 automatic sequencer (Perkin Elmer Applied Biosystems, Foster City, CA, USA) utilizing standard methods. Where possible, after initial amplification of the Qs product, the 3' region of the nSSU rDNA was sequenced using primer G06 (Saunders & Kraft, 1994). This sequence, which spans approximately 450 bp and includes the V9 variable region of the gene (Neefs et al, 1993), has been found to be a useful proxy for overall variation in the whole nSSU in Porphyra (Broom et al, 1999).…”
Section: Molecular Analysismentioning
confidence: 99%